Symbolic Construction of Queer Identities in Victorian Queer Cinema - Sun, Wenxiao; Abdullah, Karmilah; Ong, Sharon Yong Yee (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This article analyzes the symbolic construction of queer identities in Sarah Waters' Neo-Victorian Trilogy using content analysis and film semiotics. It explores postmodern narrative techniques and the symbolism of femininity, emphasizing themes of desire, identity, and redemption. The study highlights how Waters' works contribute to the nuanced portrayal of queer characters and their impact on contemporary visual storytelling.